FORMULASI SAMPO PERASAN JERUK PURUT (Citrus hystrix D.C) DAN UJI AKTIVITAS ANTI KETOMBE TERHADAP JAMUR PENYEBAB KETOMBE (Pityrosporum ovale) SECARA IN VITRO: ANTI KETOMBE - atika wahyuni (Jurnal Penelitian Farmasi Indonesia, 2017)
Dandruff is characterized by the presence of excessive flaking of dead skin flakes on the scalp and one cause is the Pityrosporum ovale fungi. Kaffir lime (Citrus hystrix D.C) is a natural material which contains antifungal namely flavonoids and saponins. This research aims to make formula preparation kaffir lime shampoo with three variations of the concentration of 10%, 15% and 20% as well as to find out the effectiveness of kaffir lime shampoo preparation to Pityrosporum ovale fungi. The results showed anti dandruff shampoo preparations kaffir lime on the first week of activity in inhibiting the growth of a Pityrosporum ovale fungi drag 20.9 mm diameter are produced by FI concentration of 10%; 21,5 mm by FII with a concentration of 15%; 21,7 mm produced by FIII with a concentration of 20% and after eight weeks the whole formula does not have activity as an anti dandruff. Based on the evaluation of the material of the shampoo anti dandruff formula whole Kaffir lime has a stable physical properties during storage. One-way ANOVA test showed that there is a significant difference in the diameters of the zones of inhibition is then followed by the tukey test and obtained the highest results inhibition zone diameter is indicated by a positive control with active substances ketoconazole 2% the diameter of the inhibition zone 22.8 mm and the kaffir lime shampoo dosage concentrations of 20% (FIII) inhibition zone diameter 21.7 mm.